Analisis Proses Pengambilan Keputusan Konsumen E-commerce Shopee di Lingkungan RT08/RW10 Sriamur Bekasi - Iffah Zubaidah; Muhammad Jamil Latief (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
Nowadays consumers are faced with so many choices in meeting their needs and desires. E-commerce seems to be a fast way to fulfill consumer shopping desires. Shopee is one of the E-commerce sites that offers a wide variety of products to consumers. This study aims to determine the online consumer buying process at Shopee. This type of research is qualitative using the interview method. The subjects of this study consisted of four informants with different backgrounds. The analysis was carried out by dividing two types of data, namely primary data from direct interviews and secondary data from relevant articles. The results showed that in the consumer purchasing decision-making process there are five stages, namely the first stage of need recognition, the second stage of seeking information, the third stage of evaluation, the fourth stage of purchase, and the fifth stage of post-purchase behavior. The process of making consumer purchasing decisions is carried out in different ways based on each one.